FACTORS DETERMINING QUALITY OF LIFE IN THE OPIATE ADDICTS POPULATION - Marinkovic, Mirjana; Đorđević Jovanović, Lidija; Đorđević, Miodrag; Karanikolić, Vesna; Novak, Sonja; Radić, Milca (Acta medicae Medianae, 2024)
It is possible that gaining an understanding of the factors that influence the quality of life of opiate addicts may improve both the quality of therapy and its overall effectiveness. There is a correlation between the many treatment facets and overall healthcare attributes, which results in a variable quality of life. In addition to the characteristics of the addiction, other aspects of the addict's life, such as demographics, socioeconomic status, and health, may also have an impact on the addict's quality of life. The purpose of this research is to determine whether or not certain characteristics of addicts, addiction, and treatment have a predictive influence on the quality of life of opiate addicts who were treated using the two approaches that are the most common.Epidemiological cross-sectional research was performed in 2020 on a random sample of 70 opiate addicts treated at University Clinical Center Niš (35 addicts in the methadone maintenance program and 35 addicts treated with buprenorphine). Using standardized World Health Organization (WHO) instruments for measuring health status (EQ-5D), severity of addiction consequences (ASI), and quality of life (WHOQOL), the necessary data were collected through "face-to-face" interviews with respondents based on an independently developed questionnaire, from which health indices were calculated (EQ-5D Index), severity of addiction consequences (Addiction Severity Index), and quality of life (WHOQOL-BREF Index). The data were presented using appropriate descriptive statistics techniques, and group differences were evaluated using the χ2 test (Chi-squared test) and t-test. Using multiple regression and correlation, predictors were extracted.In terms of the quality of life index values, there was no significant difference between addicts who were treated with methadone and addicts who were not treated with methadone. However, the former reported experiencing a much worse quality of life compared to the latter. Health traits, characteristics of respondents' socioeconomic positions, and other addiction-related outcomes were the most prominent factors in the degree to which one's quality of life was affected. The effects of the treatment were becoming less noticeable. Methadone treatment had a predictive influence on the addict's outlook on life as well as the addict's degree of satisfaction with both their psychological state and their surrounding environment. The duration of methadone therapy as well as any breaks in care were the two most important indicators. The consequences of methadone therapy on both the body and society were, on the whole, rather mild.It is impossible for a single predictor to account for variations in both the degree and the perception of quality of life across a number of different aspects. The number of aspects that are considered is rather high, and the implications that follow from this are complex.
Keywords: opiate addicts, treatment, quality of life, predictors